Dialogism and psychotherapy: therapists’ and clients’ beliefs supporting monologism - Gonçalves, Miguel M. (2006)
This article discusses how the distinction proposed by Bakhtin between monologism and dialogism can be applied to psychotherapy. According to the Bakhtinian approach, complete monologism is impossible in human interaction, given the responsive nature of humans. It is, however, possible to structure psychotherapy so that it leans towards monologism, resulting in a reduction of the diversity of voices or perspectives that can be “heard” in sessions. This attempt to suppress dialogism can occur given the hierarchical nature of the therapeutic relationship and can be reinforced by therapist and client beliefs that support monologism. In the second part of the article we discuss a set of beliefs from therapists and clients that support this conception of psychotherapy as a monological endeavor.